Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T18:41:24+01:00

A= 3x-y
B= x-1
C= -3x-y
a) A+B=3x-y+x-1=4x-y-1
b)A+B-C=4x-y-1+3x+y=7x-1
c)A-B-C=3x-y-x+1+3x+y=5x+1
d)A-(B-C)=3x-y-(x-1+3x+y)=3x-y-x+1-3x-y=-x-2y+1
2010-02-14T18:45:13+01:00
A=3x-y
B=x-1
C=-3x-y

a]A+B=3x-y+x-1=4x-y-1
b]A+B+C=3x-y+x-1-3x-y=x-2y-1
c]A-B-C=3x-y-(x-1)-(-3x-y)=3x-y-x+1+3x+y=5x+1
d]A-(B-C)=3x-y-[(x-1)-(-3x-y)]=3x-y-(x-1+3x+y)=3x-y-x+1-3x-y=
-x-2y+1
2010-02-14T18:47:29+01:00
A) A+B
3x-y+x-1=4x-y-1

b)A+B-C
(3x-y)+(x-1)-(-3x-y)
= 3x-y+x-1+3x+y
=7x-1

c)A-B-C
(3x-y)-(x-1)-(-3x-y)=
3x-y-x+1+3x+y=
=5x+1
d)A-(B-C)
(3x-y)-[(x-1)-(-3x-y)]=
3x-y-(x-1+3x+y)=
= 3x-y-x+1-3x-y=
=-x-2y+1